Branding Hunan Province as an International Travel Destination: An Analysis of the Potential E-marketing Strategies towards Taiwan Market - Yang, Ruiyin (2010)
In 2008, the agreement between Mainland China and Taiwan of building Interactive Relationship of the Economic Trade was implemented, which created positively economic effect on both sides as well as improved the cross-relations.